The Nexus of Regional Poverty and Education in Egypt: A Micro Analysis - Nassar, Heba; Biltagy, Marwa (International Journal of Economics and Financial Issues, 2016)
The poverty pattern has changed from an urban/ rural pattern to a geographical/regional pattern. These changes may be explained by several aspects. The employment aspect is one of the main determinants for socioeconomic status. The inability of household members to participate in income-generating activities is considered an important explanation of poverty trends and the relationship between poverty and employment can be explained by the loss of earnings or the decline in real incomes. This can be related to several aspects, pattern of jobs and its regularity, human resource development indicators and investment indicators. The objective of this paper is to understand the changes in poverty levels in Egypt in total and by region by studying their relationship to regional composition and trends of employment and educational characteristics. The study starts a theoretical review about poverty and employment, which will constitute the basis for the micro level analysis in order to propose a framework for a pro-poor employment strategy. Keywords: Regional Poverty; Education; Egypt; Investment in Schooling JEL Classifications: H75, I20, I32